2012
DOI: 10.1002/jbm.b.32790
|View full text |Cite
|
Sign up to set email alerts
|

Development of Portland cement for orthopedic applications, establishing injectability and decreasing setting times

Abstract: The injectability of Portland cement (PC) with calcium chloride and calcium nitrate additives was investigated using a syringe with a 2 mm aperture for potential clinical applications such as vertebroplasty. Addition of either additive at 10 wt % increased the quantity of cement extruded through the syringe from approximately 25 wt % for the PC standard, to over 95 wt %. 10 wt % additions of either additive also decreased setting times from over 2 h to below 25 min. The compressive strength of the modified cem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…This material is basically composed by Portland cement (PC), a calcium silicate‐based material (CS) added to a radiopacifying agent, bismuth oxide (BO), in a 4:1 proportion . It has been reported that PC exhibits biocompatibility and high compressive strength allowing that this material may be also suitable for medical indications, such as in orthopedic applications …”
Section: Introductionmentioning
confidence: 99%
“…This material is basically composed by Portland cement (PC), a calcium silicate‐based material (CS) added to a radiopacifying agent, bismuth oxide (BO), in a 4:1 proportion . It has been reported that PC exhibits biocompatibility and high compressive strength allowing that this material may be also suitable for medical indications, such as in orthopedic applications …”
Section: Introductionmentioning
confidence: 99%
“…MTA is basically composed by Portland cement (PC) which has physicochemical, antimicrobial and biological properties similar to commercially available MTA [3][4][5] . PC shows biocompatibility and high compressive strength allowing that this material may be suitable for medical indications, such as orthopedic applications 6) .…”
Section: Introductionmentioning
confidence: 99%
“…PC is characterized by stable biocompatibility, high compressive strength, rapid set-up, and low solubility to blood. This allows PC to be useful in providing initial graft stability in medical orthopedic applications 34. Concerning dental applications, PC is a main component of mineral trioxide aggregate (MTA), which is already widely used in endodontic surgery including root end filling, root repair, and pulp capping due to its biological and physicochemical properties 56.…”
Section: Introductionmentioning
confidence: 99%